IDENTIFICAÇÃO DOS PERÍODOS DE SECA NA AMAZÔNIA ATRAVÉS DE ENTROPIA DE PERMUTAÇÃO DAS QUEIMADAS - FERREIRA, Diego Vicente de Souza; SILVA, Antonio Samuel Alves; STOSIC, Tatijana; STOSIC, Borko (Brazilian Journal of Biometrics, 2017)
In this work we study the temporal variability of the daily number of hot pixels recorded by sattelites NOOA-12 and AQUA in the Brazilian Amazon during the period 1999{2012. While the highest peak in daily hot pixel frequencies was observed in 2007, coincident with a severe drought, for other intense droughts such as that occurred in 2005 and 2010, the corresponding number of hot pixels recorded was compatible or lower than that reached during the other years with no reported severe drought. On the other hand, we nd that the severe droughts coincide with the increase of Permutation Entropy of hot pixel time series indicating that the dynamics of the of daily hot pixels is influenced by drought events. The coincidence of the increase of entropy values with drought events suggests more disorder and less predictability of the hot pixel time series during the driest periods.